Impacto das mudanças na legislação ambiental em áreas de preservação permanente no município de Campina do Monte Alegre – SP - Godoy, Luan Rodrigues de (Universidade Federal de São Carlos)
Over the past centuries, territorial expansion and the growth of agricultural and livestock activities have caused extensive loss of Brazil’s native vegetation. In São Paulo, approximately 73% of the original vegetation has been cleared. This study analyzed native vegetation cover, modeled hydrological Permanent Preservation Areas (PPAs), and evaluated riparian forest adequacy within these areas under the environmental regulations of 1965, 1989, and 2012 in Campina do Monte Alegre, São Paulo. Geoprocessing and remote sensing techniques were employed using topographic map and satellite image interpretation in QGIS. Native vegetation reached its greatest extent in 1965 (≈2,594 ha), decreasing by 29% by 1989, and later expanding 23% by 2012 due to the emergence of smaller forest fragments. The 1989 regulation defined broader and stricter PPA criteria, yielding the largest PPA area (2,282.47 ha). Nonetheless, riparian vegetation adequacy remained low across all years, not exceeding 38% in 2012.
Impact of changes in environmental legislation on permanent preservation areas in the municipality of Campina do Monte Alegre, São Paulo
Keywords: Código florestal; Lei de proteção da vegetação nativa; Avaliação temporal.; Forestry bill; Native vegetation protection law; Temporal assessment; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; 13. Ação contra a Mudança Global do Clima